Etika Pemasyaran Syariah Perspektif Al Qur’an - Suwarno (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research aims to delve into the ethics of Sharia marketing from the perspective of the Qur'an, utilizing a qualitative method, particularly the content analysis approach through literature studies. The primary focus is to explore the concepts and principles of Sharia marketing ethics revealed in the Qur'an and analyze their relevance in the context of modern global business. The results of the research indicate that the Qur'an serves as a rich intellectual resource for formulating the framework of Sharia marketing ethics. Specific verses elucidate values such as honesty, justice, transparency, and service, forming the foundation of Sharia marketing ethics in line with Islamic principles. This study contributes to a deeper understanding of the implementation of Sharia marketing ethics in contemporary business practices. Therefore, it provides a basis for the development of a more dignified marketing paradigm in line with Islamic principles, moving from theory to practical application in shaping an ethical and sustainable business culture.